Risk Perception, Communication and Behaviour Towards Food Safety Issues - Diogo Thimoteo da Cunha (Foods)
“In spite of over 100 years of research and millions of dollars spent, food safety remains a worldwide public health issue (Christoper Griffith cited in Yiannas (2009) [...]